Pandangan Muhammad Husein Az-Zahabi Dalam Tafsir Wal Mufassirun Terhadap Kitab Tafsir Mafatihul Ghaib Karya Fakhruddin Ar-Razi - Abdul Aziz,; Haliamatussa’diyah,; Rahmat Hidayat, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The development of tafsir bi al-ra'yi (interpretation based on reasoned opinion) has yielded numerous works with diverse methodologies, reflecting the inclinations of their authors, including Fakhruddin Ar-Razi's seminal tafsir, Mafatihul Ghaib. This article critically examines Muhammad Husein Adz-Dzahabi's analysis and critique of Mafatihul Ghaib, which serves as a prime representation of permissible rational exegesis. Employing a qualitative, library research methodology, this study primarily draws upon the Qur'an and Adz-Dzahabi's Al-Tafsir wa al-Mufassirun (Vol. 1, pp. 205-210), supplemented by secondary literature including books, journals, and articles. The findings reveal that while Adz-Dzahabi acknowledges Ar-Razi's polymathic brilliance and the intellectual monument that is Mafatihul Ghaib, his fundamental critique posits that the work transcends conventional tafsir, becoming a victim of its author's own multidisciplinary genius. Adz-Dzahabi's critique underscores the crucial balance between expanding intellectual discourse and maintaining fidelity to the primary purpose of scriptural interpretation. The critical analysis of his perspective encompasses six key aspects: issues of textual authority and authenticity; the methodological strength in munasabah (inter-textual coherence); the obscuring of exegetical essence by dominant multidisciplinary discourses; a contradictory stance towards the Mu'tazilah and the presentation of theological doubts; tendencies toward excessive inference and forced correlations; and the work's ambiguous position between a Qur'anic commentary and an encyclopedia of rational sciences.